Answer:
61.2
Explanation:
To solve this, we would have to use the arithmetic progression formula
S(n) = a + (n - 1) d, where
S(n) = is the value of the nth term
a = value of the first term
n = the nth term we're interested in
d = difference between successive terms
We're given that the first term, a1 = 1.we also know that the 6th term, a6 = 44
If so, we can use this to get our "d", saying
44 = 1 + (6 - 1) d
where
44 is the value of the 6th term, and n is 6. Also, the first term a = 1. Simplifying further we have
44 = 1 + 5d
5d = 44 - 1
5d = 43
d = 43/5
d = 8.6
This means that the difference between successive term is 8.6, we then use this "d" to find our 8th term
S(n) = 1 + (8 - 1) 8.6
S(n) = 1 + 7 * 8.6
S(n) = 1 + 60.2
S(n) = 61.2
Therefore, the 8th term is 61.2